Preserving Privacy using Column Masking and Data Encryption Techniques - Lakshmi, B; Ravindra Babu, H; Krishna, Murali (International Journal of Computer Sciences and Engineering, 2025)
Information Technology plays an important role in Multi-National corporations with thousands of computer systems to small business organizations with a single system. Every business organization maintains IT Sector which is charged with maintaining and monitoring information. As rapid increase in information technology and omnipresent of internet has caused information breaches to grow faster. An information breach is a security incident in which confidential data of the organization has been stolen and used by unauthorized personnel. Information breaches may involve financial, personal information such as credit card or bank details, personal identification details, health insurance details and trade secret information of organizations. So protecting such confidential data has become a vital and integral part of each and every organization. This paper deals with security breaches, vulnerabilities in information systems and demonstrates security with column masking and data encryption techniques.